The potential of induced pluripotent stem cell derived hepatocytes - Hannoun, Z; Steichen, C; Dianat, N; al., E (Elsevier, 2016)
Orthotopic liver transplantation remains the only curative treatment for liver disease. However, the number of patients who die while on the waiting list (15%) has increased in recent years as a result of severe organ shortages; furthermore the incidence of liver disease is increasing worldwide. Clinical trials involving hepatocyte transplantation have provided encouraging results. However, transplanted cell function appears to often decline after several months, necessitating liver transplantation. The precise aetiology of the loss of cell function is not clear, but poor engraftment and immune-mediated loss appear to be important factors. Also, primary human hepatocytes (PHH) are not readily available, de-differentiate, and die rapidly in culture. Hepatocytes are available from other sources, such as tumour-derived human hepatocyte cell lines and immortalised human hepatocyte cell lines or porcine hepatocytes. However, all these cells suffer from various limitations such as reduced or differences in functions or risk of zoonotic infections. Due to their significant potential, one possible inexhaustible source of hepatocytes is through the directed differentiation of human induced pluripotent stem cells (hiPSCs). This review will discuss the potential applications and existing limitations of hiPSC-derived hepatocytes in regenerative medicine, drug screening, in vitro disease modelling and bioartificial livers.